MANAGEMENT OF PROJECT RISK IN INFORMATION TECHNOLOGY - Fraga e Silva Junior, Luiz Carlos (2013)
The companies has adopted the information technology (IT) in a more and more  intensive and inclusive way, as a powerful tool for improving their strategic and operational competitive bases. The IT has performed a fundamental role in the organizations, allowing the increasing of efficiency and synergy, through a crescent connectivity, that changes the relationship with customers, suppliers, competitors and business partners, promoting productivity improvements and changes on products and services. The IT projects are a manner found by the companies to implement resources and changes, in a planned way, searching for reaching their strategic, managerial and operational objectives. However, several researches show that the failure rates in this area stay high worldwide, due to its complex and peculiar nature, together with the uncertainties of the current economic scenario. This scenario makes essential the usage of tools and methods for increasing the success chances of the projects, and the risk management may contribute to that once it involves a full policy, a methodology and techniques to identify, qualify, quantify, plan actions and monitor events that may deviate a project from its objectives. This paper reviews the literature about the theme and analyzes how the project risk management is applied by IT professionals in the Vale do Paraíba, São Paulo, Brazil and which are the risk factors often found in the projects developed in that region. From this analysis, a checklist is created for risk identification, seeking to support the IT managers in the tasks of increasing the chances of a suitable conclusion of their projects.